Counting on commitment; the quality of primary care-led diabetes management in a system with minimal incentives - Mc Hugh Sheena; Marsden Paul; Brennan Carmel; Murphy Katie; Croarkin Celine; Moran Joe; Harkins Velma; Perry Ivan J (BMC, 2011)
Abstract Background The aim of the present study was to assess the performance of three primary care-led initiatives providing structured care to patients with Type 2 diabetes in Ireland, a country with minimal incentives to promote the quality of care. Methods Data, from three primary care initiatives, were available for 3010 adult patients with Type 2 diabetes. Results were benchmarked against the national guidelines for the management of Type 2 diabetes in the community and results from the National Diabetes Audit (NDA) for England (2008/2009) and the Scottish Diabetes Survey (2009). Results The recording of clinical processes of care was similar to results in the UK however the recording of lifestyle factors was markedly lower. Recording of HbA1c, blood pressure and lipids exceeded 85%. Recording of retinopathy screening (71%) was also comparable to England (77%) and Scotland (90%). Only 63% of patients had smoking status recorded compared to 99% in Scotland while 70% had BMI recorded compared to 89% in England. A similar proportion of patients in this initiative and the UK achieved clinical targets. Thirty-five percent of patients achieved a target HbA1c of < 6.5% (< 48 mmol/mol) compared to 25% in England. Applying the NICE target for blood pressure (≤ 140/80 mmHg), 54% of patients reached this target comparable to 60% in England. Slightly less patients were categorised as obese (> 30 kg/m2) in Ireland (50%, n = 1060) compared to Scotland (54%). Conclusions This study has demonstrated what can be achieved by proactive and interested health professionals in the absence of national infrastructure to support high quality diabetes care. The quality of primary care-led diabetes management in the three initiatives studied appears broadly consistent with results from the UK with the exception of recording lifestyle factors. The challenge facing health systems is to establish quality assurance a responsibility for all health care professionals rather than the subject of special interest for a few.